Mfn2 deletion in brown adipose tissue protects from insulin resistance and impairs thermogenesis. (24th May 2017) - Mahdaviani, Kiana; Benador, Ilan Y; Su, Shi; Gharakhanian, Raffi A; Stiles, Linsey; Trudeau, Kyle M; Cardamone, Maria; Enríquez‐Zarralanga, Violeta; Ritou, Eleni; Aprahamian, Tamar; Oliveira, Marcus F; Corkey, Barbara E; et al.
Abstract: BAT‐controlled thermogenic activity is thought to be required for its capacity to prevent the development of insulin resistance. This hypothesis predicts that mediators of thermogenesis may help prevent diet‐induced insulin resistance. We report that the mitochondrial fusion protein Mitofusin 2 (Mfn2) in BAT is essential for cold‐stimulated thermogenesis, but promotes insulin resistance in obese mice. Mfn2 deletion in mice through Ucp1‐cre (BAT‐Mfn2‐KO) causes BAT lipohypertrophy and cold intolerance. Surprisingly however, deletion of Mfn2 in mice fed a high fat diet (HFD) results in improved insulin sensitivity and resistance to obesity, while impaired cold‐stimulated thermogenesis is maintained. Improvement in insulin sensitivity is associated with a gender‐specific remodeling of BAT mitochondrial function. In females, BAT mitochondria increase their efficiency for ATP‐synthesizing fat oxidation, whereas in BAT from males, complex I‐driven respiration is decreased and glycolytic capacity is increased. Thus, BAT adaptation to obesity is regulated by Mfn2 and with BAT‐Mfn2 absent, BAT contribution to prevention of insulin resistance is independent and inversely correlated to whole‐body cold‐stimulated thermogenesis. Synopsis: Deletion of Mfn2 in BAT improves glucose tolerance under high fat diet while impairing cold‐induced thermogenesis. Therefore, BAT therapeutic potential to improve insulin sensitivity may be achieved independently of thermogenesis. Mfn2 in BAT is required to sustain body temperature after cold‐exposure. Mfn2 deletion in BAT protects from obesity‐induced insulin resistance and increases whole body lipid oxidation. In obesity, Mfn2 deletion in BAT promotes a gender‐specific remodeling of BAT mitochondria and metabolism to increase ATP synthesis capacity. Abstract : Deletion of Mfn2 in BAT improves glucose tolerance under high fat diet while impairing cold‐induced thermogenesis. Therefore, BAT therapeutic potential to improve insulin sensitivity may be achieved independently of thermogenesis.